2008
DOI: 10.1016/j.neuroscience.2007.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and cyclic-AMP regulated phosphoprotein-32–dependent modulation of prefrontal cortical input and intercellular coupling in mouse accumbens spiny and aspiny neurons

Abstract: The roles of DARPP-32 in mediating dopamine (DA)-dependent modulation of corticoaccumbens transmission and intercellular coupling were examined in mouse accumbens (NAC) neurons by both intracellular sharp electrode and whole cell recordings. In wildtype (WT) mice bath application of the D2-like agonist quinpirole resulted in 73% coupling incidence in NAC spiny neurons, compared to baseline (9%), whereas quinpirole failed to affect the basal coupling (24%) in slices from DARPP-32 knockout (KO) mice. Thus, D2 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 99 publications
(203 reference statements)
0
2
0
Order By: Relevance
“…D1 receptors affect GABA neurotransmission 33 and D1 agonism increases NMDA receptor trafficking 34 . DARPP32 itself mediates NMDA trafficking, and facilitates non-synaptic communication between neurons 35 . Connecting DARPP32 back to EE, it was recently reported that 24 h EE resulted in changes in spine morphology in the nucleus accumbens.…”
Section: Discussionmentioning
confidence: 99%
“…D1 receptors affect GABA neurotransmission 33 and D1 agonism increases NMDA receptor trafficking 34 . DARPP32 itself mediates NMDA trafficking, and facilitates non-synaptic communication between neurons 35 . Connecting DARPP32 back to EE, it was recently reported that 24 h EE resulted in changes in spine morphology in the nucleus accumbens.…”
Section: Discussionmentioning
confidence: 99%
“…In the retina, the regulator is a neuromodulator, dopamine: Light triggers the release of dopamine, which closes gap junctions via second messengers (McMahon et al, 1989 ; Dong and McReynolds, 1991 ; Weiler et al, 2000 ). Dopamine, as well as noradrenaline and histamine, have been found to open and close gap junctions in several of these brain areas (Cepeda et al, 1989 ; Yang and Hatton, 2002 ; Onn et al, 2008 ; Zsiros and Maccaferri, 2008 ).…”
Section: Discussionmentioning
confidence: 99%